Systematic Review on the Use of Indian Gooseberry in Improvement of Oral Hygiene - Surya Rajeev Nair, S.Shree Lakshmi, B harathwaj.V.V, Sindhu.R , Raj Mohan, D. Prabu ,M.Dinesh Dhamodhar (Drugs and Cell Therapies in Hematology, 2021)
Background: Oral health is regarded as a key indicator of an individual's overall health and well-being. Indian gooseberry is a plant widely used in Ayurveda medicine for the treatment of various diseases. In addition, it increases immunity against various diseases. Aim: To evaluate the effectiveness of Indian gooseberry in improving oral hygiene.Study design: Systematic reviews of the existing literature are performed. Results: Electronic and hand search engines retrieved 151 records. In this study, these interventions and outcomes were assessed after scrutinisation. Three studies were included in this systematic review which showed adequate results to prove the effectiveness of Indian gooseberry. Conclusion: It was concluded that Indian gooseberry could increase antimicrobial activity and improve oral hygiene.